Thesis-Building: Architecture, Alchemy and the Constructive Moment(s) of a Doctoral Dissertation - Willem de Bruijn (Footprint)
This paper looks back at the long and sometimes difficult process of doing a ‘PhD’. It asks how certain ‘moments’ in the building of a doctoral thesis – moments of conception, of discovery, of despair, of truth, of revelation and of jouissance – inform the building of a thesis. By revisiting these moments, the paper traces the genesis of the author’s thesis on Architecture and Alchemy and explores the metaphor of construction encountered in the work of cultural theorist Walter Benjamin.